Predicting compressive strength of high-performance concrete with high volume ground granulated blast-furnace slag replacement using boosting machine learning algorithms - Rathakrishnan V.; Bt. Beddu S.; Ahmed A.N. (Nature Research, 2023)
algorithm; article; compressive strength; furnace; machine learning; prediction error; slag